Primary pancreatic hydatid cyst; typical radiological signs: A case report - Mohsen, Shalal; Mohammed, Nader; Abd El Wahab Abo Dakika, Muhammad; Abdel Nour Adeab Gawargios, Fayrouz (Indian Journal of Case Reports, 2024)
Pancreatic hydatid cysts are rare, especially in pediatric populations, and their diagnosis presents a remarkable challenge because of the non-specific clinical presentation and the limitations of available diagnostic tools, particularly in resource-limited settings. Our case highlights the importance of maintaining a high index of suspicion for hydatid disease, even in pediatric patients presenting with non-specific abdominal symptoms, particularly in rural regions, where diagnostic resources may be limited. Early recognition and accurate diagnosis are crucial for guiding appropriate therapeutic interventions and preventing potential complications associated with this rare but clinically significant entity.